Making Southeast Asia Visible: Restoring the Region to Global History - Keck, Stephen L (수완나부미, 2020)
Students of global development are often introduced to Southeast Asia by reading many of the influential authors whose ideas were derived from their experiences in the region. John Furnivall, Clifford Geertz, Benedict Anderson and James Scott have made Southeast Asia relevant to comprehending developments far beyond the region. It might even be added that others come to the region because it has also been the home to many key historical events and seminal social developments. However, when many of the best-known writings (and textbooks) of global history are examined, treatment of Southeast Asia is often scarce and in the worst cases non-existent. It is within this context that this paper will examine Southeast Asia’s role in the interpretation of global history. The paper will consider the ‘global history’ as a historical production in order to depict the ways in which the construction of global narratives can be a reflection of the immediate needs of historians. Furthermore, the discussion will be historiographic, exhibiting the manner in which key global histories portrayed the significance of the region. Particular importance will be placed on the ways in which the region is used to present larger historical trajectories. Additionally, the paper will consider instances when Southeast Asia is either profoundly underrepresented in global narratives or misrepresented by global historians. Last, since the discussion will probe the nature of ‘global history’, it will also consider what the subject might look like from a Southeast Asian point of view. The paper will end by exploring the ways in which the region’s history might be augmented to become visible to those who live outside or have little knowledge about it. Visual augmented reality offers great potential in many areas of education, training and heritage preservation. To draw upon augmented reality as a basic metaphor for enquiry (and methodology) means asking a different kind of question: how can a region be “augmented” to become (at least in this case) more prominent. That is, how can the region’s nations, histories and cultures become augmented so that they can become the center of historical global narratives in their own right. Or, to put this in more familiar terms, how can the “autonomous voices” associated with the region make themselves heard?